PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY MATERI SISTEM PENCERNAAN PADA MANUSIA UNTUK SISWA KELAS 5 SDN BULUSARI 3 - Fitrianty, Dewi Devanda; Putri, Kharisma Eka; Laila, Alfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students' understanding of the human digestive system material at SDN Bulusari 3 is still low, one of the causes is the minimal use of interactive learning media that can present the material in a real and easy to understand manner. The purpose of this study was to determine (1) the validity, (2) practicality, and (3) the effectiveness of the development of Augmented Reality learning media for the human digestive system material for 5th grade students of SDN Bulusari 3. The method used was R&D with the ADDIE model. Data collection techniques in this study used questionnaires and tests. The data obtained were then analyzed using a Likert scale. Validity data were obtained from questionnaires from media experts and material experts. Practicality data were obtained from questionnaires from teachers and students. Effectiveness data were obtained from post-test results compared with KKM and classical completeness. The results of the study showed that (1) AR media was declared very valid with a media validation score percentage of 89.4% and material validation of 100%. (2) The results of the teacher's practicality questionnaire were 96% and students 95%, both in the very practical category. (3) The effectiveness results obtained a score of 95.26%, which is included in the very effective category. Based on these results, the development of AR learning media for human digestive system material for 5th grade students of SDN Bulusari 3 has proven to be very valid, practical, and effective. Thus, this media is suitable for use as an interactive learning tool.